LEGALITAS BAWASLU KABUPATEN/KOTA : STUDI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 48/PUU-XVII/2019 Muhammad Bastari Mauludi - Mauludi, Muhammad Bastari (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2021)
In 2020, the Constitutional Court issued the Constitutional Court Decision Number 48/PUU-XVII/2019 regarding the Legality of the Regency/City Election Oversight Body. The Constitutional Court's decision gave rise to overlaps between the Election Law and the Regional Head Election Law. so that the problems that arise are related to the legality of the Regency/City Bawaslu before and after the Constitutional Court Decision Number 48/PUU-XVII/2019. This study uses a qualitative method (library research) combined with empirical research methods by extracting information from the opinion of informants about the Legality of Regency/City Bawaslu. And the results of the research are the Changes in the Nomenclature of Regency/City Bawaslu as a monitoring agency for the implementation of elections that are permanent and independent according to those stated in Law Number 7 of 2017. And do not use the local election Law as the basis for establishing Regency/City Bawaslu.